Sodobne informacijske tehnologije in storitve: OTS 2019: zbornik štiriindvajsete konference, 18. in 19. junij 2019 (University of Maribor Press, 2019)
Advanced Information Technology and Services: OTS 2019: Proceedings of the Twenty-fourth Conference, 18th - 19th of June, 2019. The papers in the proceedings of the 24th Professional Conference on Advanced Information Technology and Services address the extremely topical challenges that we (IS/IT experts, Software Engineers, Computer Scientists, Data Scientists, software and solution architects, developers, IT managers, etc.) encounter in our daily work. The authors present the innovative solutions and rich experience gained by conducting real-life projects: Applying Augmented Intelligence and Machine Learning technologies, Using Blockchain technologies and platforms, Developing loosely coupled micro-services, Providing full virtualization and exploitation of distributed infrastructures, Ensuring cybersecurity, confidentiality and privacy, Applying large-scale agile methods in distributed teams, Introducing agile approaches that enable the rapid and efficient software development via automated processes, and continuous testing, integration, delivery & deployment Updating and upgrading existing Information Systems, Incorporating advanced programming languages and development environments, Developing user-friendly web and mobile solutions & services.